Extended Electrochemical Window of Solid Electrolytes via Heterogeneous Multilayered Structure for High‐Voltage Lithium Metal Batteries. Issue 12 (31st January 2019) - Duan, Hui; Fan, Min; Chen, Wan‐Ping; Li, Jin‐Yi; Wang, Peng‐Fei; Wang, Wen‐Peng; Shi, Ji‐Lei; Yin, Ya‐Xia; Wan, Li‐Jun; Guo, Yu‐Guo
Abstract: In response to the call for safer high‐energy‐density storage systems, high‐voltage solid‐state Li metal batteries have attracted extensive attention. Therefore, solid electrolytes are required to be stable against both Li anode and high‐voltage cathodes; nevertheless, the requirements still cannot be completely satisfied. Herein, a heterogeneous multilayered solid electrolyte (HMSE) is proposed to broaden electrochemical window of solid electrolytes to 0–5 V, through different electrode/electrolyte interfaces to overcome the interfacial instability problems. Oxidation‐resistance poly(acrylonitrile) (PAN) is in contact with the cathode, while reduction tolerant polyethylene glycol diacrylate contacts with Li metal anode. A Janus and flexible PAN@Li1.4 Al0.4 Ge1.6 (PO4 )3 (80 wt%) composite electrolyte is designed as intermediate layer to inhibit dendrite penetration and ensure compact interface. Paired with LiNi0.6 Co0.2 Mn0.2 O2 and LiNi0.8 Co0.1 Mn0.1 O2 cathodes, which are rarely used in solid‐state batteries, the solid‐state Li metal batteries with HMSE exhibit excellent electrochemical performance including high capacity and long cycle life. Besides, the Li||Li symmetric batteries maintain a stable polarization less than 40 mV for more than 1000 h under 2 mA cm −2 and effective inhibition of dendrite formation. This study offers a promising approach to extend the applications of solid electrolytes for high‐voltage solid‐state Li metal batteries. Abstract : A heterogeneous multilayered structure that expands the electrochemical window of solid electrolytes is designed. The oxidation‐resistant poly(acrylonitrile) (PAN) and reduction‐tolerant polyethylene glycol diacrylate integrated with the Janus and flexible PAN@Li1.4 Al0.4 Ge1.6 (PO4 )3 (80 wt%) composite electrolyte broaden the electrochemical window to 0–5 V, resulting in excellent performance for high‐voltage solid‐state Li‐metal batteries. Additionally, the thickness of electrolyte is below 25 μm.